(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article presents the importance of professional competence for teachers of a special educational institution, its social necessity, components of competence, internal and external factors influencing its formation, pedagogical conditions and technologies associated with the formation of competence associated with the profession of a teacher.